Situation Report: Romania, 8 October 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Regime Efforts to Stop Rural Migration Ministry of Forestry Administration and Construction Materials The New Schoolyear Begins Reactions to the Beirut Massacre Ion Gheorghe Maurer Turns 80 Difficulties in Metallurgy First Romanian-Built BAC 1-11Jet Airliner Romanian Construction Abroad